2019
DOI: 10.1177/1043986219894431
|View full text |Cite
|
Sign up to set email alerts
|

Compensating for Sexual Identity: How LGB and Heterosexual Australian Police Officers Perceive Policing of LGBTIQ+ People

Abstract: Police officers are highly criticized for their differential policing of people categorized by identity. One such group who has experienced differential policing is the lesbian, gay, bisexual, transgender, intersex, and queer (LGBTIQ+) community. Contributing new knowledge to the extant policing literature regarding intersectional identities of Australian police officers and perceptions of policing, this research applies Social Identity Theory to understand differences between lesbian, gay, bisexual, and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Government and police agencies themselves have recognized there is a need to address the strained relationship between law enforcement and the LGBTQ community, and have implemented training across the United States to do so (Copple & Dunn, 2017; President’s Task Force on 21st Century Policing, 2015). For example, research that directly surveyed police officers on their perceptions of LGBTQ individuals revealed that some endorse stereotypical or biased attitudes toward the LGBTQ community (Bernstein & Kostelac, 2002; Israel et al, 2017; Miles-Johnson & Death, 2020) which has the potential to manifest into discriminatory behavior toward LGBTQ individuals (Herek, 1995). Unfortunately, though, many of these training programs are dissolved due to budgetary constraints (Israel et al, 2016), were received with mixed results (Israel et al, 2017), or were misunderstood as the LGBTQ community wanting “special treatment” by police officers (Sumner & Sexton, 2016).…”
Section: Perceptions Of Policementioning
confidence: 99%
“…Government and police agencies themselves have recognized there is a need to address the strained relationship between law enforcement and the LGBTQ community, and have implemented training across the United States to do so (Copple & Dunn, 2017; President’s Task Force on 21st Century Policing, 2015). For example, research that directly surveyed police officers on their perceptions of LGBTQ individuals revealed that some endorse stereotypical or biased attitudes toward the LGBTQ community (Bernstein & Kostelac, 2002; Israel et al, 2017; Miles-Johnson & Death, 2020) which has the potential to manifest into discriminatory behavior toward LGBTQ individuals (Herek, 1995). Unfortunately, though, many of these training programs are dissolved due to budgetary constraints (Israel et al, 2016), were received with mixed results (Israel et al, 2017), or were misunderstood as the LGBTQ community wanting “special treatment” by police officers (Sumner & Sexton, 2016).…”
Section: Perceptions Of Policementioning
confidence: 99%
“…Researchers have looked at how police personnel feel toward transgender people and other members of the LGBTIQ+ community (Miles-Johnson & Death, 2019). In order to enhance policing procedures and protect the safety and well-being of transgender individuals, these studies have underlined the need of understanding the attitudes and opinions of police officers towards the transgender community (Miles-Johnson & Death, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%